TDLAS-Based Rapid and Accurate Measurement of Near-Ambient Temperature Using Near-Infrared Vibrational Water Vapor Transitions - Jiaao Zhang; Jiao Gao (Sensors)
Tunable diode laser absorption spectroscopy (TDLAS) of water vapor transitions has been used to effectively measure temperature under high temperature and pressure conditions. However, due to the weak variation in transmittance and low signal-to-noise ratio, applying the same technique to measure temperature in near-ambient environments is difficult. This study reports the rapid and accurate measurement of near-ambient temperature through monitoring water vapor transitions with a three-point measurement method based on TDLAS. The transmission spectra of two selected water vibrational transitions at 1389.01 and 1389.89 nm are investigated, and the monotonic variations in the dip area are validated both theoretically and experimentally. The results show that by using the proper regression parameter (RatiodipA/RatiodipB)2, the temperature measurement time can be reduced to 40 s, with an uncertainty as low as 0.39 °C and a p-value as small as 1.98 × 10−13. This work contributes to rapid and accurate non-invasive temperature measurement in near-ambient complex environments.